THE CONCEPT OF CHINESE-INDONESIAN-NESS AS SEEN FROM ERNEST PRAKASA’S ROLES IN NGENEST, CEK TOKO SEBELAH, SUSAH SINYAL AND STIP & PENSIL - Sutandio, Anton; Angjaya, Sonny (Seni Media Rekam ISI Surakarta, 2019)
This article discusses four films entitled Ngenest (2015), Cek Toko Sebelah (2016), Susah Sinyal (2017), and Stip & Pensil (2017) in which Ernest Prakasa played a role, in the context of how the four films construct Chinese-Indonesian-ness. In the context of cinema, the appearance of Chinese-Indonesians on the screen during the New Order regime was scarce, and if there is any, the depiction was highly stereotyped. Only after Reform era in the late 1990s that Chinese-Indonesians and their culture began to re-appear on screen. Ernest Prakasa is one of few Chinese-Indonesians who publicly celebrates his Chinese-ness through entertainment platform. Ethnic identity theory applied on the discussion of the film cinematography and mise-en-scene to show what the films say about the concept of Chinese-Indonesian-ness. The findings show that Prakasa not only celebrates being a Chinese-Indonesian, but he also performs a self-mockery as Chinese-Indonesians by explicitly emphasizing the Chinese-Indonesians stereotypes. He also tries to re-establish inter-ethnic relationship and introduce contemporary Chinese-Indonesian-ness concept through his films.